ISPC commentary on the WLE Phase II Preproposal (2017-2022) - CGIAR Independent Science and Partnership Council (CGIAR Independent Science and Partnership Council, 2015)
ISPC commentary on the Water, Land and Ecosystems (WLE) Phase II Preproposal (2017-2022)